2005
DOI: 10.1055/s-2005-864155
|View full text |Cite
|
Sign up to set email alerts
|

New Cytotoxic Cyclobutanoid Amides, a New Furanoid Lignan and Anti-Platelet Aggregation Constituents fromPiper arborescens

Abstract: Three new cyclobutanoid amides with trans-trans-trans configurations, piperarborenine C, piperarborenine D and piperarborenine E, and a new furanoid lignan, (+)-arborone, together with twelve known compounds, were isolated from the stems of Piper arborescens. The structures of these new compounds were determined by means of spectral analyses. Piperarborenine C, (+)-diayangambin, piplartine, piperolactam B, piperolactam C, aristolactam BIII, goniothalactam, and methyl trans-3,4,5-trimethoxycinnamate possessed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
73
0
14

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(88 citation statements)
references
References 11 publications
(17 reference statements)
1
73
0
14
Order By: Relevance
“…Several of them have been reported to show cytotoxic activity towards tumor cell lines (5). Piperine has been reported to display central nervous system depressant, antipyretic, analgesic, and anti-inflammatory activities (3).…”
Section: Introductionmentioning
confidence: 99%
“…Several of them have been reported to show cytotoxic activity towards tumor cell lines (5). Piperine has been reported to display central nervous system depressant, antipyretic, analgesic, and anti-inflammatory activities (3).…”
Section: Introductionmentioning
confidence: 99%
“…Piplartine has shown significant cytotoxicity against cell tumor lines, as well as antifungal, antimitotic and anti-platelet aggregation compound. [9][10][11][12][13] Piplartine anticancer potential has been highlighted by the undergoing preclinical evaluation. In vivo studies using murine tumors demonstrated that in spite of a moderate anticancer activity, piplartine has weak toxicological side effects.…”
mentioning
confidence: 99%
“…Several of them have been reported to be cytotoxic activity towards tumor cell lines [2]. Piperine has been reported to display central nervous system depressant, antipyretic, analgesic, and anti-inflammatory activities.…”
Section: Introductionmentioning
confidence: 99%
“…It is metabolized in the liver by hepatic CYP3A4 activity. Piperine, a major plant alkaloid, has been shown to inhibit the CYP3A [2], enzymatic activity in a cell-free system. In a study, it was observed piperine and docetaxel could increase docetaxel's pharmacokinetic activity in vitro and in vivo.Docetaxel is one of the most commonly used cytotoxic chemotherapeutic agents.…”
Section: Introductionmentioning
confidence: 99%